2012
DOI: 10.1134/s0020168513010032
|View full text |Cite
|
Sign up to set email alerts
|

Phosphors based on NaZr2(PO4)3-type calcium and strontium phosphates activated with Eu2+ and Sm3+

Abstract: International audienceCa0.5Zr2(PO4)3:Eu2+, Sr0.5Zr2(PO4)3:Eu2+, and Ca0.5Zr2(PO4)3:Eu2+, Sm3+ orthophosphates prepared through precipitation using sol-gel processes are analogs of NaZr2(PO4)3 (NZP) and crystallize in space group R Their crystallographic parameters determined by X ray diffraction are consistent with the interatomic distances extracted from EXAFS data. Their luminescence spectra obtained under excitation in the range 300-400 nm contain emission bands between 425 and 525 nm. Substitution of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…Masaaki Hirayama has reported the luminescence properties of Eu 2+ ions doped alkaline earth zirconium phosphate A 0.5 Zr 2 (-PO 4 ) 3 (A = Ca, Sr, Ba) prepared by co-precipitation method in reduction atmosphere [19]. Glorieux has studied the Ca 0.5Àx Zr 2 (-PO 4 ) 3 (0 6 x 6 0.5), Sr 0.3 Eu 0.2 Zr 2 (PO 4 ) 3 , and Ca 0.2 Eu 0.1 Sm 0.133 Zr 2 (-PO 4 ) 3 phosphates and codoping with Eu and Sm has ensured luminescence with chromaticity coordinates approaching those of white light: (x = 0.27, y = 0.34) [20]. Zhu et al has synthesized CaZr 4 (PO 4 ) 6 :Eu by high temperature solid-state reaction in air, and found the photoluminescence (PL) emission spectrum shows both broad Eu 2+ emission at 496 nm and the characteristic sharp line emissions of Eu 3+ ions from 580 to 700 nm [21].…”
Section: Introductionmentioning
confidence: 96%
“…Masaaki Hirayama has reported the luminescence properties of Eu 2+ ions doped alkaline earth zirconium phosphate A 0.5 Zr 2 (-PO 4 ) 3 (A = Ca, Sr, Ba) prepared by co-precipitation method in reduction atmosphere [19]. Glorieux has studied the Ca 0.5Àx Zr 2 (-PO 4 ) 3 (0 6 x 6 0.5), Sr 0.3 Eu 0.2 Zr 2 (PO 4 ) 3 , and Ca 0.2 Eu 0.1 Sm 0.133 Zr 2 (-PO 4 ) 3 phosphates and codoping with Eu and Sm has ensured luminescence with chromaticity coordinates approaching those of white light: (x = 0.27, y = 0.34) [20]. Zhu et al has synthesized CaZr 4 (PO 4 ) 6 :Eu by high temperature solid-state reaction in air, and found the photoluminescence (PL) emission spectrum shows both broad Eu 2+ emission at 496 nm and the characteristic sharp line emissions of Eu 3+ ions from 580 to 700 nm [21].…”
Section: Introductionmentioning
confidence: 96%
“…The open and strongly bonded structure makes possible the fast movement i.e., the high mobility of the Na + ions tunnelling through polyhedra chain (O 3 ZrO 3 (Na)ZrO 3 O 3 ). [9][10][11] In order to synthesize thermally stable efficient luminescent materials, the incorporation of the f-block element in the NASICON structure has been carried out by several researchers. The downconversion luminescence study based on the lanthanide doped (Eu 2+ , Sm 3+ ) NASICON materials has been reported for a broad range of applications, including white light emitting diodes (WLEDs).…”
Section: Introductionmentioning
confidence: 99%
“…There are two types of cavities available for stocking cations, one position of M1 type and three positions of M2 type, which are different in size, shape and environment. In the general form, NZPphosphates are described by a crystal-chemical formula of (M1) [6] (M2) [8] 3 {L [6] 2 (PO 4 ) 3 } ∞ (figures in square brackets are the coordination numbers of cations in the corresponding positions) [1].…”
Section: Introductionmentioning
confidence: 99%
“…Lanthanides can also be included in the non-frame positions, like the series of phosphates Ln 0.33 Zr 2 (PO 4 ) 3 , where Ln = Ce-Lu (space group P 3c) [4]. Systems of solid solutions such as B II 0.5−x Eu x Zr 2 (PO 4 ) 3 , (B II -Ca, Sr, Ba) [6][7][8][9], Ca 0.5−1.5x Sm x Zr 2 (PO 4 ) 3 [6] and Ca 0.5−1.5(x+y) Er x Yb y Zr 2 (PO 4 ) 3 [7] with the NZP structure containing calcium, strontium, barium and lanthanides Eu 2+ , Sm 3+ , Er 3+ , Yb 3+ in the cavity positions M1 have been investigated as a basis for luminescent materials having emissions in different light spectrum ranges and for obtaining white light [6][7][8][9]. However, the available data on the role of the environment of Ln 3+ , its arrangement in the positions of the NZP structure and on the influence of the environment on luminescence properties are limited.…”
Section: Introductionmentioning
confidence: 99%